Implementation of Ngebel Lake Tourism Development as a Leading Natural Tourist Destination in Ponorogo District - Shakti, Titus Wirangga; Al Ghifari, Rifqi Putra; Fitri, Anisa Mamba'ul; Hardjati, Susi (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
The tourism sector is a major contributor to the country"™s foreign exchange which is mainstay of the Government of the Republic Indonesia. One of which is The Ponorogo Regency itself is known for its Ngebel Lake, which has been designated as a leading natural tourism destination. This research focuses on the implementation of the Ponorogo Regency Regional Regulation Number 4 of 2021 on Tourism Villages for the development and management of Ngebel Lake as a leading natural tourism destination in Ponorogo. This study uses a descriptive-qualitative method and the theory of public policy implementation according to George C. Edward III. The informants of this study were elements of the Ngebel Sub-District Government, elements of the Ponorogo Youth and Sports Culture Tourism Office and business actors around the Ngebel Lake tourist area. Data collection in this study used interview, observation and documentation techniques with data validity using triangulation to obtain valid data. The results of the research show that there is well established and continuous communication, arrangements that are carried out according to their functions and responsibilities, resources that are clearly used as they should be, and an appropriate bureaucratic structure. The results of the research show that the Ponorogo Regency Regulation No. 4 of 2021 on Tourism Villages is well implemented in the management and development of the Ngebel Lake Tourist Area, with the caveat that the government, through relevant agencies, must continue to pay attention to aspects of accessibility to and from tourist areas.